Clinical characteristics of patients with the hardware failure after surgical stabilization of rib fractures in Korea: a case series - Na Hyeon Lee; Sun Hyun Kim; Seon Hee Kim; Dong Yeon Ryu; Sang Bong Lee; Chan Ik Park; Hohyun Kim; Gil Hwan Kim; Youngwoong Kim; Hyun Min Cho (Journal of Trauma and Injury)
Purpose Surgical stabilization of rib fractures (SSRF) is widely used in patients with flail chests, and several studies have reported the efficacy of SSRF even in multiple rib fractures. However, few reports have discussed the hardware failure (HF) of implanted plates. We aimed to evaluate the clinical characteristics of patients with HF after SSRF and further investigate the related factors. Methods We retrospectively reviewed the electronic medical records of patients who underwent SSRF for multiple rib fractures at a level I trauma center in Korea between January 2014 and January 2021. We defined HF as the unintentional loosening of screws, dislocation, or breakage of the implanted plates. The baseline characteristics, surgical outcomes, and types of HF were assessed. Results During the study period, 728 patients underwent SSRF, of whom 80 (10.9%) were diagnosed with HF. The mean age of HF patients was 56.5±13.6 years, and 66 (82.5%) were men. There were 59 cases (73.8%) of screw loosening, 21 (26.3%) of plate breakage, 17 (21.3%) of screw migration, and seven (8.8%) of plate dislocation. Nine patients (11.3%) experienced wound infection, and 35 patients (43.8%) experienced chronic pain. A total of 21 patients (26.3%) underwent reoperation for plate removal. The patients in the reoperation group were significantly younger, had fewer fractures and plates, underwent costal fixation, and had a longer follow-up. There were no significant differences in subjective chest symptoms or lung capacity. Conclusions HF after SSRF occurred in 10.9% of the cases, and screw loosening was the most common. Further longitudinal studies are needed to identify risk factors for SSRF failure.